Hyperfine-driven persistent currents in mesoscopic rings based on a 2D electron gas with Rashba spin-orbit interaction - Cherkaskiy, Vitaliy A.; Shevchenko, Sergey N.; Rozhavsky, Alexander S.; Vagner, Israel D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
We present a detailed theory of induced persistent current (PC) produced by hyperfine interaction in mesoscopic rings based on a 2 D electron (hole) gas in the absence of external magnetic field. PC emerges due to combined action of the hyperfine interaction of charge carriers with polarized nuclei, spin-orbit interaction and Berry phase.